Identification of Novel Laminin- and Fibronectin-binding Proteins by Far-Western Blot: Capturing the Adhesins of Streptococcus suis Type 2 - Li, Quan; Liu, Hanze; Du, Dechao; Yu, Yanfei; Ma, Caifeng; Jiao, Fangfang; Yao, Huochun; Lu, Chengping; Zhang, Wei (Frontiers in Cellular and Infection Microbiology, 2015)
Bacterial cell wall (CW) and extracellular (EC) proteins are often involved in interactions with extracellular matrix (ECM) proteins such as laminin (LN) and fibronectin (FN), which play important roles in adhesion and invasion. In this study, an efficient method combining proteomic analysis and Far-Western blotting assays was developed to screen directly for bacterial surface proteins with LN- and FN-binding capacity. With this approach, fifteen potential LN-binding proteins and five potential FN-binding proteins were identified from Streptococcus suis serotype 2 (SS2) CW and EC proteins. Nine newly identified proteins, including oligopeptide-binding protein OppA precursor (OppA), elongation factor Tu (EF-Tu), enolase, lactate dehydrogenase (LDH), fructose-bisphosphate aldolase (FBA), 3-ketoacyl-ACP reductase (KAR), Gly ceraldehyde-3-phosphate dehydrogenase (GAPDH), Inosine 5′-monophosphate dehydrogenase (IMPDH), and amino acid ABC transporter permease (ABC) were cloned, expressed, purified and further confirmed by Far-Western blotting and ELISA. Five proteins (OppA, EF-Tu, enolase, LDH, and FBA) exhibited specifically binding activity to both human LN and human FN. Furthermore, seven important recombinant proteins were selected and identified to have the ability to bind Hep-2 cells by the indirect immunofluorescent assay. In addition, four recombinant proteins, and their corresponding polyclonal antibodies, were observed to decrease SS2 adhesion to Hep-2 cells, which indicates that these proteins contribute to the adherence of SS2 to host cell surface. Collectively, these results show that the approach described here represents a useful tool for investigating the host-pathogen interactions.